Light quark contributions to the nucleon electromagnetic form factors; Journal of Physics G: Nuclear and Particle Physics; Vol. 41, iss. 9 - Obukhovsky I. T.; Faessler A.; Gutsche T.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2014, 2014)
Title screen